Itinerários, estruturas de sociabilidades e ação política: intelectuais de São Paulo na crise do Império (1875-1889) - Correa, Rubens Arantes [UNESP] (2014)
The context of crisis Empire started in 1870 and culminated with the outcome of the civil - military movement that overthrew the monarchy in 1889 was lived intensely, in São Paulo, by a group of men of letters attached to emerging economic sectors and eager for prestige and visibility in a highly conservative society and nobility. Led a movement concatenated and intentional political confrontation against the dominant status through manifestos, classist conferences, clubs and political parties, Masonic brotherhoods, news organizations, interventions in the fields of education and culture, structures from which they built networks sociability and repertoires of ideas . The political action of the men of letters paulistas aimed to put in place a power project that was able to contemplate interests located, for which forged a repertoire within which the term republic functioned more as a call to co-opt accessions towards your project power and much less as a belief and conviction in the republican values of citizenship, respect for public affairs, separation between public and private, and universalization of individual liberties. At the end of the day the motion is revealed and the winner group of intellectuals of São Paulo prospective members of the new political order after proclamation of the republic emerged. It is intended here working hypothesis that the group of São Paulo intellectuals built a repertoire of confronting the imperial political status from their experiences and sharing that appeal to large listed the time as republic, abolitionism positivism etc., was only a strategy of accommodation of group interests in a context of decline of hegemonic forms of power which the group members was conscious and sought to take advantage